DUTIES AND AUTHORITIES OF THE REGIONAL REPRESENTATIVES (DPRD) IN THE IMPLEMENTATION OF BUDGET FUNCTION ON THE REGIONAL REVENUE AND EXPENDITURE BUDGET (APBD) OF CENTRAL JAVA PROVINCE - Avitta Karunia Dewi (Berkala Akuntansi dan Keuangan Indonesia, 2020)
This research discusses the Duties and Authorities of the Regional People's Representative Council (DPRD) particularly in budgeting function, the obstacles, and efforts to overcome these problems. This paper uses a qualitative case study. Data were derived from interviews and literature study. The results showed that the DPRD Central Java has an important role in budgeting. The obstacles arising are related to limited funds, adjusting time, schedule, and different activities between DPRD members, and other aspect like communication. The efforts made to overcome these obstacles include increasing funds, adjusting time and activity, as well as encouragement from the Deliberative Council, therefore all DPRD members attend at the APBD discussion with the executive.